Does Globalization Cause Environmental Degradation in Developing Economies? Evidence from Cote d’Ivoire Using Ecological Footprint - KEHO, Yaya (International Journal of Energy Economics and Policy, 2023)
This research examines the effects of globalization on environmental degradation in Cote d’Ivoire using data from 1970−2018. Previous studies in this area mostly focused on carbon emissions as indicator for environmental degradation. However, this study uses ecological footprint to cover different aspects of environmental degradation. Using the autoregressive distributed lag approach, the results disclose that globalization worsens the environmental quality by increasing ecological footprint. Furthermore, the results demonstrate a positive and monotonic relationship between economic growth and ecological footprint. The decomposition of globalization into different dimensions reveals that economic, social and political globalization contribute to environmental degradation. On the basis of the findings, some recommendations are suggested to tackle environmental degradation.